2023
DOI: 10.3390/antiox12020414
|View full text |Cite
|
Sign up to set email alerts
|

Honey’s Antioxidant and Antimicrobial Properties: A Bibliometric Study

Abstract: Research attention has been drawn to honey’s nutritional status and beneficial properties for human health. This study aimed to provide a bibliometric analysis of honey’s antioxidant and antimicrobial properties. The research advancements within this field from 2001 to 2022 were addressed using the Scopus database, R, and VOSviewer. Of the 383 results, articles (273) and reviews (81) were the most common document types, while the annual growth rate of published manuscripts reached 17.5%. The most relevant topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…It also prevents chronic inflammatory conditions, such as atherosclerosis. [13][14][15] In this study, the antioxidant activities of different honey types collected from two different areas in Jordan were determined (Figure 1). To assess the antioxidant capacity of honey samples; the total phenolic contents, free radicals scavenging activity, and reducing power were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…It also prevents chronic inflammatory conditions, such as atherosclerosis. [13][14][15] In this study, the antioxidant activities of different honey types collected from two different areas in Jordan were determined (Figure 1). To assess the antioxidant capacity of honey samples; the total phenolic contents, free radicals scavenging activity, and reducing power were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The naturally occurring antibacterial agents abaecin, defensin-1, apidaecin, and hymenoptaeci are all included in these bee peptides. Additionally, honey incorporates bee pollen into its composition [81,82].…”
Section: Honey-derived Peptide Defensin-1 Produced By Bees As An Anti...mentioning
confidence: 99%
“…It serves as a crucial component of the immune system, safeguarding against harmful pathogens [85,86]. Additionally, defensin-1 exhibits antioxidant properties by effectively neutralizing free radicals and preventing oxidative stress-related damage [38,81]. Studies have demonstrated that defensin-1 plays a role in enhancing the antioxidant capacity of honey and other products derived from bees [81].…”
Section: Antioxidant Properties Of the Peptide Defensin-1: Final Remarksmentioning
confidence: 99%
“…Globally, intensive research on antimicrobial (against antibiotic susceptible and resistant bacterial strains in humans) and antioxidant properties of honey including its bioactive chemical constituents has been carried out in Asia, Europe, and America, with Africa still lagging [ 14 ]; albeit a high number of endemic and medicinal plant species reported in the African continent when compared to others [ 15 ]. It is not fully understood how these biological activities together with the phytochemical constituents vary among different African honeys, and how they compare with those of the highly valued Manuka honey.…”
Section: Introductionmentioning
confidence: 99%